A retrospective analysis of unprotected ultraviolet tolerance and influencing factors in 1036 participants evaluating the efficacy of cosmetic sunscreen products - Yingge Chen; Jiaying Du; Siyi Wang; Mengxuan Zhang; Qishi Xu; Guolin Chen; Tao Zhang; Yu Sun (Journal of Dermatologic Science and Cosmetic Technology, 2025)
Objective: To more rapidly and accurately obtain minimal erythema dose (MED) and minimal persistent pigment dose (MPPD) values in sun protection testing, we conducted a retrospective exploration of previous test data. Methods: This retrospective study analyzed sunscreen test data collected from January 1, 2021, to September 1, 2024, among long-term East Asian residents in Shenzhen, China. We investigated correlations between skin color characteristics, age, seasonal variations, and UV sensitivity indicators (MED and MPPD). Results: The results indicate that in the population tested, there is a significant negative correlation between ITA° and the unprotected MED of participants (P < 0.05), but no statistical correlation with the unprotected MPPD (P > 0.05). There was a minimal correlation between participant age and both unprotected MED and MPPD. When compared to the other seasons, participants in winter exhibited significantly higher unprotected MED (P < 0.05), and the unprotected MPPD was significantly higher in the autumn and winter than in spring and summer (P < 0.05). Conclusion: In conclusion, defining proprietary predictive MED and MPPD values based on laboratory test population data in sunscreen efficacy testing enhances the probability of actual values conforming to preset gradients, thereby improving test success rates and overall efficiency. Moreover, while the impact of age is relatively minor, differences in skin color, population, and season do affect the results of MED and MPPD, which in turn influence the outcomes of sun protection product testing. Therefore, it may be necessary to conduct customized sun protection capability tests tailored to the product's target demographic and environmental context.